Conceptualizing religion and spirituality in secular schools: a qualitative study of Alberta schooling - McKinnon, M (2015)
Over most of the 20th Century, many educational systems around the world became increasingly secular, notably with lessening involvement of religious institutions. However, what it means to offer secular education to an increasingly diverse student population is emerging as a contemporary international educational issue. The face of immigration, the rights of Aboriginals, and increasingly diverse and individual forms of religiosity and spirituality have implications for secular education today. This qualitative study of Alberta schooling provides an example of a setting that underwent a high degree of secularization in the 1960's-1980's. A litigious but interpretive boundary exists for the extent educationists were to engage students in thinking about religion and spirituality. Yet, teachers operated with a high degree of autonomy. With these contextual factors as a backdrop, this study explored how a hierarchical sample of Alberta policy-makers, administrators, and teachers conceptualized religion and spirituality for secular secondary schools. Results show that Alberta Education conceptualized space for the conservative religious and Aboriginal communities, but not mainstream students. The students operated in a 'leave your faith at the door' secular model, curriculum was rationalized, and the function of schooling was perceived as preparing students for work. Findings show that principals and teachers challenged the lack of space for mainstream students to engage in the concepts of religion and spirituality. They argued the secular model disadvantaged mainstream students in exercising their right to religious freedom and developing religious literacy and sensitivity skills and it also prevented non-religious students from gaining access to religious/spiritual concepts and tools to facilitate wellbeing and resiliency.